Development of Student Worksheets for Biology Learning Based on Higher Order Thinking Skill (HOTS) for the Second Grade (XI) of Senior High School: in Case to Respiratory System Material - Suci, Isnaini Tiara; Rasyidah, Rasyidah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This study aims to develop a Student Worksheet based on Higher Order Thinking Skills that is feasible, practical and effective to use. This research is Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The data analysis technique used is a combination of quantitative and qualitative. Quantitative data analysis was used to determine the feasibility, practicality, and effectiveness. Meanwhile, qualitative data analysis was used to determine the results of observations, inputs and suggestions. The output of this study stated that the HOTS-based Student Worksheet on the respiratory system sub-material was declared eligible to be tested with revisions. The development of HOTS-based Student Worksheet is applicable with a score of 98.46% (Media Validator) and is considered very feasible with a percentage of 85.3% (Material Validator). The practicality of Student Worksheet is indicated by the teacher response rate of 98.3% and the student response rate of 84.02%. This Student Worksheet also declared effective with an N-gain value of 0.32 in the medium category. Based on the results obtained, the HOTS-based Student Worksheet was declared feasible, practical and effective to be applied in learning activities.